Use of low-dose UV-C irradiation to control powdery mildew caused by Podosphaera aphanis on strawberry plants. Issue 4 (1st October 2016) - Janisiewicz, Wojciech J.; Takeda, Fumiomi; Nichols, Breyn; Glenn, D. Mike; Jurick II, Wayne M.; Camp, Mary J.
Abstract: Strawberry powdery mildew, caused by Podosphaera aphanis, significantly reduces fruit yield and quality and predisposes fruit to other diseases. Fungicides have been routinely used to control this disease; however, their limitations necessitate the development of alternative approaches, especially for protective culture and organic production. A disease-control strategy was developed that combines treating strawberry plants with a low dose of UV-C (low dose/short duration) followed by a specific period of darkness, which greatly increases the lethality of UV-C. A leaf disc assay was developed to evaluate the effectiveness of the UV-C treatment in controlling powdery mildew on strawberry. Irradiation for only 15 s by UV-C lamps with an output of 20.6 µW cm − 2 followed by a 4-h dark period resulted in a significant decrease ( P  = 0.05) in P. aphanis as determined by the percentage of the leaf disc quadrants colonized by the fungus. An increase in irradiation exposure to 60 s followed by 4-h dark period resulted in complete control of the powdery mildew in most cases. Such treatment of strawberry plants once a week for 3 weeks resulted in more than a four-fold reduction ( P  = 0.01) of conidial production on adaxial leaf surfaces exposed to the UV-C irradiation, and did not affect leaf photosynthesis ( P  = 0.05). The UV-C treatment of plants over 15 weeks reduced the amount of diseased fruit and increased fruit yield and quality ( P  = 0.05).